2018
DOI: 10.1108/ijm-04-2016-0083
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between flexible employment arrangements and workplace performance in Great Britain

Abstract: Purpose-There is an increasing concern on the quality of jobs and productivity witnessed in the flexible employment arrangements. The aim of this study is to examine the relationship between various flexible employment arrangements and the workplace performance. Design/Methodology-Home-based working-teleworking, flexible timing and compressed hours are the main employment types examined using the Workplace Employee Relations Survey (WERS) over the years 2004 and 2011 in Great Britain. The workplace performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 36 publications
1
38
0
4
Order By: Relevance
“…Also, people working in different home environments (family type) will have an impact on the conflict they face. Through the insights we got on specific needs for individual (Achievement, Power or Affiliation), we can try to reduce the impact of conflict that an individual might face and this can contribute towards longevity of employee engagement and improving the performance of individual (Giovanis, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, people working in different home environments (family type) will have an impact on the conflict they face. Through the insights we got on specific needs for individual (Achievement, Power or Affiliation), we can try to reduce the impact of conflict that an individual might face and this can contribute towards longevity of employee engagement and improving the performance of individual (Giovanis, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The impacts of various factors that affect the performance of an employee and their job satisfaction while teleworking need to be evaluated. Firm performance is shown to be positively related to workplace flexibility (Giovanis, 2018) and teleworking, which can be explained by liberation from fixed temporal schedules, and may require an employee to work for more hours to cope up with work overload. Teleworking may enable employees with time and spatial flexibility and also increase organisational flexibility required during uncertainty; thus, a positive relation was showed to exist between telework adoption and flexible work options (Sánchez, Pérez, de Luis Carnicer, & Jiménez).…”
Section: Need-based Motivation and Its Relationship With Wthc And Htwcmentioning
confidence: 99%
“…Flexi hours scheme offers the control to the beginning and ending of the work schedule. It facilitates employees to fulfil their non-labor commitments including childcare, household chores or personal activities, (Giovanis, 2018). where an employee could choose their starting and ending working hours and enjoy its benefits.…”
Section: Flexible Hoursmentioning
confidence: 99%
“…(Baeza, Gonzalez, & Wang , 2018), how people feel about their jobs, is usually their work attitude, indicating their job satisfaction, not only reflects an overall opinion about a worker's well-being, but relationship to important outcomes. (Giovanis, 2018) reported that flexible working arrangements provides employees control over their jobs and autonomy, in work-life balance and job satisfaction resulting in increased productivity. Evidences shows that flexibilities provide balance between work and life especially during parenthood, .…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation